Understanding the bond-making and bond-breaking of Fe-filled SWNT on Ni(111) - David, Melanie Yadao (Animo Repository, 2008)
In the previous studies, the stable structures and magnetic properties of Fe-filled single-walled carbon nanotubes (SWNTs) on Ni(111) were investigated based on first principles calculations. The SWNT transformed into arch-like structure when the Fe atom was placed inside it near the Ni surface.In order to fully understand the formation of nanoarch when placed near the metal surface, we have provided a detailed mechanism of the bond-breaking of SWNT and the bond-making of SWNT-Fe and Ni surface.The electron distributions and the number of electrons in the majority and minority spins per atomic orbital were discussed. Copyright © 2008 John Wiley & Sons, Ltd.